CT-based volumetric tumor growth velocity: A novel imaging prognostic indicator in oropharyngeal cancer patients receiving radiotherapy. (December 2016) - Perni, Subha; Mohamed, Abdallah S.R.; Scott, Jacob; Enderling, Heiko; Garden, Adam S.; Gunn, G. Brandon; Rosenthal, David I.; Fuller, Clifton D.
Highlights: CT-based volumetric assessment of oropharyngeal tumor growth velocity is proposed. Velocity is calculated from pretreatment scans with time gap of more than 2 weeks. Velocity ⩾ 1% per day is predictive of worsened disease control and survival. In presumed HPV-related tumors, higher velocity is not predictive of outcomes. Higher nodal growth velocity is associated with distant metastases. Abstract: Objectives: Volumetric tumor growth velocity (TGV) reflects in vitro tumor aggressiveness, but its prognostic value has not been investigated in vivo. We examined the prognostic impact of TGV on oncologic outcomes in patients with oropharyngeal squamous cell cancer (OSCC). Materials and methods: 101 OSCC patients with two pretreatment CTs with time gap of 2 or more weeks treated at a single institution between 2004 and 2008 were identified. Primary tumor and nodal targets were segmented in scans. Linear growth rates were calculated. Recursive partitioning analysis (RPA) identified cut point associated with outcomes. Results: Median follow-up was 59 months (range 7–118). Median primary TGV was 0.65% increase per day (range 0–9.37%). RPA identified TGV cut point associated with local control (LC) of 1% per day. Patients with higher TGV had decreased 5-year LC (73% vs. 98%, p = 0.0004), distant control (DC, 62% vs. 91%, p = 0.0007), and overall survival (OS, 38% versus 93%, p < 0.0001). In multivariate analysis including demographics, tumor stage, subsite, and treatment factors, TGV ⩾ 1% per day independently predicted worsened LC (p = 0.02), DC (p = 0.003), and OS (p < 0.0001). However, this TGV cutoff was not significantly predictive of LC, DC, or OS for a subset of presumed HPV-positive patients. Conclusion: OSCC TGV ⩾ 1% per day is a substantive negative prognostic indicator for disease control and overall survival, particularly in HPV non-associated tumors. This novel CT-based volumetric assessment of TGV suggests a simple methodology for risk stratification of patients.